Spontaneous Coronary Artery Dissection in a Woman with a Past Medical History of Subarachnoid Hemorrhage: A Case Report. (2nd November 2017) - Bardon, Jean; Picard, Fabien; Barbou, Franck; Varenne, Olivier; Vivien, Benoît
Abstract: Spontaneous coronary artery dissection (SCAD) is an uncommon disease. We report the case of a 50 year-old woman with a past medical history of aneurysmal subarachnoid hemorrhage, presenting with acute chest pain and diffuse ST segment elevation on ECG. Coronary angiogram revealed a SCAD of the left anterior descending coronary artery. The association between cerebral aneurysms and SCAD should trigger providers concern for fibromuscular dysplasia. We hereby report on a rare and atypical case involving the relationship between fibromuscular dysplasia and SCAD.